Patient’s Knowledge and Attitude towards Tuberculosis in an Urban Setting - Tasnim, Saria; Rahman, Aminur; Hoque, F. M. Anamul (Pulmonary Medicine, 2012)
Tuberculosis is a public health problem in Bangladesh. This cross-sectional study was conducted to assess knowledge of TB patients about symptoms, ways of transmission and treatment of tuberculosis, and their perception of the illness. Between March and August 2008, 762 adult TB patients were interviewed at selected DOTS centre of Dhaka city. Male and female distribution was 55.6% and 44.4%, respectively. One quarter of them were illiterate, and more than half had extended family and live in a congested situation. Night fever was the most common symptom known (89.9%), and 56% were aware that it could spread through sneezing/coughing. Television was mentioned as a source of information about TB. The majority expressed a helping attitude towards other TB patients. Although most of them were positive about getting family support, 46.6% mentioned discrimination of separate utensils for food or drink. About 50.5% expressed increased sadness, 39.8% had fear of loss of job/wedges, and 21.4% felt socially neglected. Along with drug treatment the psychosocial reactions of TB patients should be addressed at DOTS centers for better control of the disease.